Spatial Pattern of Landcover Changes in Obajana Watershed, Kogi State: A GIS Approach - Adejoh, Emmanuel; Abubakar, Eleojo Oluwaseun (NIU Journal of Humanities, 2018)
This research characterizes the land use land cover of Obajana watershed and assesses the spatial pattern of land cover change in the area from 1987 to 2013. Primary and secondary data were used for the research. The primary data were index coordinates of geographic features within the study area, collected through the use of global positioning system. The secondary data were Geodetic Digital Elevation Model (GDEM) and Landsat TM / ETM imageries for three epochs (1987, 2006 and 2013) with path and row of 189 and 55 downloaded from Global Landcover Resources Website (http:www.glcf.com). Supervised image classification was done for the three series of remotely sensed imageries to extract the spatial pattern of land cover change. GIS techniques were used to derive the maps, and the various landuse systems were compared using percentage distribution. The Obajana watershed is characterized by a maximum and minimum elevations of 411 m and 134 m respectively with a two dimensional area of 43.4 km 2 . Cement production in the area was largely linked with the increase in land cover change of the watershed, with areas covered by woodland reducing by about 37% while exposed and impervious land surfaces have increased by 40% and 111%, respectively, between 1987 and 2013. Assessment of the pattern of change indicated that while impervious land surfaces were concentrated in the north-eastern and north-western axis in 1987, they shifted to the central part, spreading towards the northern and eastern axis of the study area in 2013.  The study concluded that integrating Remote Sensing and Geographic Information System (GIS) was adequate for generating spatio-temporal information for the assessment of landcover changes in the study area. Keywords : Remote Sensing, GIS, Obajana Watershed, Land use, Land cover, Change.